Pemanfaatan Macromedia Flash 8 Sebagai Media Pembelajaran Mata Kuliah Bahasa Inggris Pada mahasiswa FKIP Universitas Dehasen Bengkulu - Sari, Heni Kusnita; Yupianti, Yupianti (UNIVED Press, 2020)
Technological developments are very supportive and needed to help things run smoothly in agencies, schools or universities, as well as in decision making. Current technological developments have influenced all areas of human life and are needed as a means of support that can support precise, precise and accurate information. The aim of writing this scientific work is to deliver a course at FKIP PTIK, Dehasen University, Bengkulu, so that it can provide a new atmosphere in teaching and learning precisely, quickly and accurately. So with this, multimedia is one of the means to convey material to each student so that students do not feel bored when receiving lessons given by Mr. and Mrs. Lecturer, which can create better results in delivering lessons because it combines text, graphics, audio, image. Based on the results of making learning media for English courses at FKIP, Dehasen University, Bengkulu using Macromedia Flash 8, it can be concluded that with the existence of learning media for English courses at FKIP, Dehasen University, Bengkulu using Macromedia Flash 8, we can help lecturers in conveying material better. easy and well understood by every student.